Self-esteem mediated relations between loneliness and social anxiety in Chinese adolescents with left-behind experience - Chen, Chen; Hu, Liangyi (Frontiers in Psychology, 2022)
Although research examining loneliness and social anxiety has been conducted, few studies have explored pathways from loneliness at home to social anxiety at school in Chinese left-behind children. The study attempts to explore associations between loneliness at home and social anxiety at school and to examine roles of self-esteem in those relationships among a sample of Chinese left-behind children. Date were collected from 303 left-behind children, aged 10–14 years, and the Chinese versions of Children’s Loneliness Scale, Social Anxiety Scale, and Rosenberg Self-esteem Scale were used to measure loneliness at home, social anxiety at school, and self-esteem, respectively. Results showed that loneliness at home was positively associated with social anxiety at school; self-esteem played a partial mediation role in associations between loneliness at home and social anxiety at school. Findings suggest that high levels of self-esteem may influence pathways from loneliness at home to social anxiety at school in Chinese left-behind children, and increasing levels of self-esteem may be used in preventions for loneliness of Chinese left-behind children.